The Effects of Temporary Services and Contracting Out on Low-Skilled Workers: Evidence from Auto Suppliers, Hospitals, and Public Schools - George Erickcek; Susan Houseman; Arne Kalleberg (W.E. Upjohn Institute for Employment Research, 2002)
We examine why employers use temporary agency and contract company workers and the implications of these practices for the wages, benefits, and working conditions of workers in low-skilled labor markets. Through intensive case studies in manufacturing (automotive supply), services (hospitals), and public sector (primary and secondary schools) industries, we define the circumstances under which these workers are likely to be adversely affected, minimally affected, or even benefitted by such outsourcing. Adverse effects on compensation are clearest when companies substitute agency temporaries or contract company workers for regular employees on a long-term basis because low-skilled workers within the organization receive relatively high compensation and employment and labor law or workers and their unions do not block companies from such substitution. Often, however, organizations only contract out management functions or utilize agency temporaries for brief periods of time, with little direct effect on in- house, low-skilled workers. Moreover, employers often use temporary agencies to screen workers for permanent positions. Because temporary agencies lower the cost to employers of using workers with poor work histories or other risky characteristics, agencies may benefit these workers by giving them opportunities to try out for positions they otherwise might not have had.
Additional information: A revised version of this paper appears in Eileen Appelbaum, Annette Bernhardt, and Richard J. Murnane, eds. Low-Wage America: How Employers are Reshaping Opportunity in the Workplace (pp. 368-406). New York: Russell Sage Foundation, 2003. Please cite the revised version.
Keywords: J31; J32; J41; J42; J45; J51; J81; K31; 330; temporary; contingent; contract; workers; low-skilled; Houseman; Erickcek; Kalleberg